Detection and quantification of anti-rabies glycoprotein antibodies: current state and perspectives - Rodríguez, María Celeste (2021)
Rabies is an ancient fatal disease with no other available treatment than post-exposure vaccination, where the bite of infected animals, mainly dogs, is the leading cause of its transmission to human beings. In this context, global vaccination campaigns of companion animals, as well as wildlife reservoirs vaccination, are key factors to achieve the “Zero by 30” plan that pursues the eradication of dog-mediated human rabies by 2030. Rabies virus-neutralizing antibodies (VNAs) play an essential role in the disease protection, as it correlates with an adequate immune response and allows evaluating pre- or post-exposure prophylaxis efficacy. Hence, counting with reliable, accurate, and robust serological tests is of paramount importance. Currently, RFFIT and FAVN are the gold standard VNAs tests recommended by both the WHO and the OIE. Despite these methodologies are efficient and widely used, they present several drawbacks, as they are less easily to standardize and require the use of live rabies virus, containment facilities, and skilled professionals. Thus, in this review, we describe the state-of-the-art of alternative analytical methodologies currently available for rabies serology, with novel approaches based on pseudotyped recombinant viruses and emphasizing in the antigen binding methodologies that detect and quantify antibodies against the rabies glycoprotein. We discussed the wide range of assays that are interesting tools for a faster measurement of anti-rabies glycoprotein antibodies and, in some cases, less complex and more versatile than the gold standard methods. Finally, we discussed the key issues during the design and optimization steps of ELISA assays, highlighting the importance of validation and standardization procedures to improve rabies serology tests and, as a consequence, their results.